Isomerisation reactions of α-methyl allyl [acetate, trifluoroacetate]: theoretical study. (1st September 2013) - Shiroudi, Abolfazl; Zahedi, Ehsan
The [3, 3]-sigmatropic rearrangement reactions of α-methyl allyl acetate (1), and α-methyl allyl trifluoroacetate (2) have been studied using ab initio molecular orbital (MO) methods at the HF, B3LYP, B3PW91, and BHandHLYP levels with a 6-31++G** basis set. Among the methods used in this study, the values for activation parameters obtained with the BHandHLYP/6-31++G** method are in good agreement with experimental values. The calculated data demonstrate that in the rearrangement reactions of the compounds studied, the polarisation of the O3–C4 bond is rate determining. Optimised transition states at the BHandHLYP/6-31++G** level were used for calculating the nucleus-independent chemical shift (NICS) and also a natural bond orbital (NBO) analysis was carried out at the same level. Based on the optimised ground state geometries using the BHandHLYP/6-31++G** method, the NBO analysis of donor – acceptor (bonding – antibonding) interactions revealed that the stabilisation energies associated with electronic delocalisation from the σO(3)–C(4) bonding orbital to the π*C(5)=C(6) antibonding orbital, increase from compounds 1 to 2. The σO(3)–C(4) →π*C(5)=C(6) resonance energies for compounds 1 and 2 are 1.59 and 1.62 kcal mol–1, respectively. Also, analysis of the donor – acceptor interactions σO(3)–C(4) →π*C(5)=C(6) suggests that in these rearrangements, the TS structure in compound 2 has more aromatic character than for compound 1. The NBO results revealed that in these rearrangements, activation energies are not controlled by the σO(3)–C(4) →π*C(5)=C(6) resonance energy. NICS results indicate that the aromaticities of the transition states are controlled by the out-of-plane component. The predicted high-pressure-limit rate constants for the rearrangement reactions of compounds 1 and 2 are represented as 6.12 × 1012 exp(–21604/T), and 1.04 × 1013 exp(–17846/T) s–1, respectively. The fall-off pressures for the rearrangement reactions 1 and 2 are found to be 9.56 × 10–5 and 1.09 × 10–3 mmHg, respectively. The fall-off pressures of compounds 1 and 2 in both reactions are in the following order: P1/2(2)>P1/2(1) and the rates follow as: rate (2)>rate (1). Analysis of bond order, NBO charges, bond indices and synchronicity parameters suggest the Claisen rearrangement reactions of 1 and 2 occur through a concerted and slightly asynchronous six-membered cyclic transition state type of mechanism.